International summit on the nutrition of adolescent girls and young women: consensus statement. Issue 1 (19th July 2017) - Krebs, Nancy; Bagby, Susan; Bhutta, Zulfiqar A.; Dewey, Kathryn; Fall, Caroline; Gregory, Fred; Hay, William; Rhuman, Lisa; Caldwell, Christine Wallace; Thornburg, Kent L.
Abstract : An international summit focusing on the difficult challenge of providing adequate nutrition for adolescent girls and young women in low‐ and middle‐income countries was held in Portland, Oregon in 2015. Sixty‐seven delegates from 17 countries agreed on a series of recommendations that would make progress toward improving the nutritional status of girls and young women in countries where their access to nutrition is compromised. Delegate recommendations include: (1) elevate the urgency of nutrition for girls and young women to a high international priority, (2) raise the social status of girls and young women in all regions of the world, (3) identify major knowledge gaps in the biology of adolescence that could be filled by robust research efforts, (4) and improve access to nutrient‐rich foods for girls and young women. Attention to these recommendations would improve the health of young women in all nations of the world.